ENDOTHELIAL CELLS EXPOSED TO UREMIC TOXINS SECRETE INTERLEUKIN-8 WHICH PROMOTES VASCULAR CALCIFICATIONS. (June 2018) - Abdallah, J. Bou; Zibara, K.; Issa, H.; Gross, P.; Langlet, G.; Six, I.; Choukroun, G.; Kamel, S.; Bennis, Y.
Abstract : Objective: Vascular calcifications (VC) contribute to arterial stiffness and atherosclerosis and are amplified during chronic kidney disease (CKD), in part due to the accumulation of uremic toxins such as phosphate (Pi) and indoxyl sulfate (IS). We hypothesized that the activation of endothelial cells (ECs) by uremic toxins promotes vascular smooth muscle cells (SMCs)-induced calcification. Design and method: HUVECs were treated with uremic concentrations of Pi, IS or both for 48 hours, then ECs conditioned media (EC-CM) was collected. Human aortic SMCs (hASMCs) were treated with the same uremic conditions, with or without EC-CM supplementation, and then viability and calcification were assayed. To identify factors secreted from ECs exposed to uremic toxins, a cytokine array (CA) was used to screen for 40 cytokines involved in osteogenic metabolism. Next, ELISA and RT qPCR were performed to evaluate IL-8 secretion and expression from ECs, since it was modulated in the CA. The IL-8 effect on hASMCs calcification was also examined by addition of human IL-8 in the media or by evaluating the procalcifying effect of EC-CM collected from ECs transfected with IL-8 siRNA. RT qPCR was also performed to examine the osteochondrogenic switch of hASMCs. Results: Pi+IS significantly decreased the viability of hASMCs by 30% that was not affected by EC-CM. Conversely, Pi+IS significantly increased the calcification of hASMCs and this effect was aggravated by EC-CM supplementation (wrt control, 3 ± 0.9 without EC-CM vs. 4.8 ± 0.7 with EC-CM, P < 0.0001). Compared to control, Pi+IS induced IL-8 gene expression in ECs (3.4 ± 1.2 fold increase, P = 0.0144) and IL-8 release from ECs (17.5 ± 7.9 pg/ml for control vs. 1.3 ± 0.2 pg/ml for Pi+IS, P = 0.0164). IL-8 addition to hASMCs under uremic exposure significantly promoted calcification in a concentration-dependent manner. Furthermore, uremic EC-CM induced-hASMCs calcification was prevented by silencing of IL-8 gene in ECs. Finally, IL-8 prevented the Pi+IS-induced increase of osteopontin gene in hASMCs (wrt control, 2.2 ± 0.2 without IL-8 vs. 1.3 ± 0.3 with IL-8). Conclusions: These results strongly suggest, for the first time, that IL-8 secreted from ECs during uremic exposure may play a critical role in vascular calcifications and thus in the cardiovascular complications of CKD.